2017
DOI: 10.1021/acs.energyfuels.7b01184
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Characterization of Tight Sandstones Using Nuclear Magnetic Resonance and Incremental Pressure Mercury Injection Experiments: Implication for Tight Sand Gas Reservoir Quality

Abstract: A series of experiments including porosity and permeability measurements, thin section and scanning electron microscopy (SEM) observations, incremental pressure mercury injection (IPMI), and nuclear magnetic resonance (NMR) were conducted to systematically characterize the pore structure of tight sandstone from the Lower Shihezi Formation of Permian (P2x) in the northeastern Ordos Basin, China. The influences of pore types, pore size distribution, and fractal characteristics on reservoir quality of tight sands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 40 publications
0
51
0
Order By: Relevance
“…Porosity is a basic physical parameter of formation rock and offers more reliable information with respect to pore volume than pore geometry. Once WPT damage has occurred and some pore space is occupied by water, less pore space is left to act as a flow channel . Since not all rock pore volume allows gas flow after water invasion, rock porosity does have some affect the WPT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porosity is a basic physical parameter of formation rock and offers more reliable information with respect to pore volume than pore geometry. Once WPT damage has occurred and some pore space is occupied by water, less pore space is left to act as a flow channel . Since not all rock pore volume allows gas flow after water invasion, rock porosity does have some affect the WPT.…”
Section: Discussionmentioning
confidence: 99%
“…Once WPT damage has occurred and some pore space is occupied by water, less pore space is left to act as a flow channel. 32 Since not all rock pore volume allows gas flow after water invasion, rock porosity does have some affect the WPT. However, as the results in Figure 9 show the relationship between rock porosity, the degree of water drainage and gas permeability damage is not particularly significant and actually shows that porosity generally has a weak influence on WPT damage and is not a vital petrophysical factor affecting WPT damage.…”
Section: Rock Porositymentioning
confidence: 99%
“…where dS hgi is the increment of total mercury intrusion corresponding to pores with a radius of r i [18]. The permeability contribution by HPMI is determined on the basis of the Purcell equation.…”
Section: Relationship Between Petrophysical Properties and Different mentioning
confidence: 99%
“…Many scholars have tried to integrate various techniques to describe the multi-scale PSD of tight sandstones [15][16][17]. Nuclear magnetic resonance (NMR) is an effective tool for non-destructively quantifying the multi-range pore structures of tight sandstone reservoirs [18][19][20], but the NMR-derived PSD related to the relaxation time (T 2 ) should be transformed to pore size (µm) through integration with other methods. The NMR-derived PSD has been determined with imaging methods (e.g., casting thin sections and field emission scanning electro microscopy (FE-SEM)) using a large amount of statistical multi-scale pore radii data [21].…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al () suggested that the sandbodies develop extensively in the study area and the reservoir quality is controlled by a variety of factors. Some studies investigated the pore structure of the Shanxi Formation sandstones using nuclear magnetic resonance and pressure‐controlled mercury injection and found that the reservoir is tight and heterogeneous (Li et al, ; Shao, Pang, Jiang, et al, ; Shao, Pang, Li, & Zhang, ). Drilling results have shown that the Shanxi Formation tight sandstones in the north‐eastern Ordos Basin have more complex mineral compositions and diagenetic characteristics than those in the central part of the basin, leading to variable reservoir quality (porosity and permeability).…”
Section: Introductionmentioning
confidence: 99%